Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Linda Mack ^ Mary Ellen Clay applauding while Lindell Cross hugs Louise Erickson and Marcia McLane